Bibliometric analysis for artificial intelligence in the internet of medical things: mapping and performance analysis - Chiroma, Haruna; Hashem, Ibrahim Abaker Targio; Maray, Mohammed (Frontiers in Artificial Intelligence, 2024)
The development in computer technology revolutionized the way people live and interact in the society. The Internet of things has brought the development of internet of medical things for the transformation of healthcare delivery. Different aspect of artificial intelligence has been used to improve the internet of medical things. Despite the significant of bibliometric analysis in a research area, to the best of the authors knowledge based on searches conducted in academic databases, no bibliometric analysis on artificial intelligence for internet of medical things has been conducted. To close this gap, this paper proposed to perform a comprehensive bibliometric analysis on the applications of artificial intelligence in internet of medical things. Bibliometric analysis of top sources of literature, main disciplines, countries, prolific authors, trending topics, authorship, citations, author-keywords and co-keywords were evaluated. In addition, the structural development of the artificial intelligence in internet of medical things showing growing popularity of the internet of medical things. It was found in the study undoubtedly that the issue of security and privacy were serious source of disquiet hindering massive adoption of the internet of medical things. Future research on internet of medical things from perspective of artificial general intelligence, generative artificial intelligence, and explainable artificial intelligence were outlined and discussed.